2018
DOI: 10.14227/dt250118p38
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Method Development and Validation for Lercanidipine Hydrochloride Tablets

Abstract: Lercanidipine hydrochloride (HCl) is L-type calcium channel blocker widely used in the management of hypertension. According to the BCS classification system, it is classified under BCS class II drugs, showing low solubility and high permeability. The dissolution profile and thus the in vivo performance of this class of drugs widely depend on their solubility and hence their behaviour in dissolution medium. Lercanidipine HCl is not official in any pharmacopeia, so no official dissolution method is available. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…In addition, the optimum CMC concentration for enzyme production was achieved at 1%. Similar results were obtained from B. thuringiensis [20] While Achromobacter xylosoxidans BSS4 and Paenibacillus barcinonensis MG7 showed maximum cellulase activity at 0.5 and 2% concentration of CMC, respectively [21], [22].…”
Section: Resultssupporting
confidence: 79%
“…In addition, the optimum CMC concentration for enzyme production was achieved at 1%. Similar results were obtained from B. thuringiensis [20] While Achromobacter xylosoxidans BSS4 and Paenibacillus barcinonensis MG7 showed maximum cellulase activity at 0.5 and 2% concentration of CMC, respectively [21], [22].…”
Section: Resultssupporting
confidence: 79%
“…The Dissolution of a solid dosage form is affected by the type and ratio of excipients, processing factors (methods of granulation and the compression force applied [8]. An in vitro dissolution test helps in formulation development, investigations for post-approval changes, quality control and post marketing surveillance [9]. Drug dissolution, a key factor in the success of therapeutic outcome of drug product, is a rate kinetic process that deals with how long it takes a solute to form a saturated solution.…”
Section: Introductionmentioning
confidence: 99%
“…Maximum bgls production was obtained when using CMC (Table 2) this result confirmed the recently reported that Bacillus sp. produced maximum cellulases production in the presence of CMC as a carbon source [3], [21], [14], [23]. This finding indicates the positive regulation effect of CMC in cellulases gene expression in Bacillus .…”
Section: Discussionmentioning
confidence: 82%